Cognitive Gains from Gist Reasoning Training in Adolescents with Chronic-Stage Traumatic Brain Injury - Cook, Lori G.; Chapman, Sandra B.; Elliott, Alan C.; Evenson, Nellie N.; Vinton, Kami (Frontiers in Neurology, 2014)
Adolescents with traumatic brain injury (TBI) typically demonstrate good recovery of previously acquired skills. However, higher-order and later emergent cognitive functions are often impaired and linked to poor outcomes in academic and social/behavioral domains. Few control trials exist that test cognitive treatment effectiveness at chronic recovery stages. The current pilot study compared the effects of two forms of cognitive training, gist reasoning (top-down) versus rote memory learning (bottom-up), on ability to abstract meanings, recall facts, and utilize core executive functions (i.e., working memory, inhibition) in 20 adolescents (ages 12-20) who were six months or longer post-TBI. Participants completed eight 45-minute sessions over one month. After training, the gist reasoning group (n = 10) exhibited significant improvement in ability to abstract meanings and increased fact recall. This group also showed significant generalizations to untrained executive functions of working memory and inhibition. The memory training group (n = 10) failed to show significant gains in ability to abstract meaning or on other untrained specialized executive functions, although improved fact recall approached significance. These preliminary results suggest that relatively short-term training (6 hours) utilizing a top-down reasoning approach is more effective than a bottom-up rote learning approach in achieving gains in higher-order cognitive abilities in adolescents at chronic stages of TBI. These findings need to be replicated in a larger study; nonetheless, the preliminary data suggest that traditional cognitive intervention schedules need to extend to later-stage training opportunities. Chronic-stage, higher-order cognitive trainings may serve to elevate levels of cognitive performance in adolescents with TBI.